Approximation by Generalized Lupaş Operators Based on q-Integers - Mohd Qasim; M. Mursaleen; Asif Khan; Zaheer Abbas (Mathematics, 2020)
The purpose of this paper is to introduce q-analogues of generalized Lupaş operators, whose construction depends on a continuously differentiable, increasing, and unbounded function <semantics> ρ </semantics> . Depending on the selection of q, these operators provide more flexibility in approximation and the convergence is at least as fast as the generalized Lupaş operators, while retaining their approximation properties. For these operators, we give weighted approximations, Voronovskaja-type theorems, and quantitative estimates for the local approximation.